2017
DOI: 10.1017/etds.2016.126
|View full text |Cite
|
Sign up to set email alerts
|

On the irregular points for systems with the shadowing property

Abstract: We prove that when f is a continuous self-map acting on a compact metric space (X, d) which satisfies the shadowing property, then the set of irregular points (i.e. points with divergent Birkhoff averages) has full entropy.Using this fact we prove that in the class of C 0 -generic maps on manifolds, we can only observe (in the sense of Lebesgue measure) points with convergent Birkhoff averages. In particular, the time average of atomic measures along orbit of such points converges to some SRB-like measure in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 44 publications
(55 reference statements)
2
43
0
Order By: Relevance
“…The following result is a simplified, one-dimensional version of [26, Proposition 2.1] (cf. [12,11]). It will be very useful in further calculations in Section 4.…”
Section: Topological Entropymentioning
confidence: 99%
“…The following result is a simplified, one-dimensional version of [26, Proposition 2.1] (cf. [12,11]). It will be very useful in further calculations in Section 4.…”
Section: Topological Entropymentioning
confidence: 99%
“…Briefly, multifractal analysis studies the dynamical complexity of the level sets of the invariant local quantities obtained from a dynamical system. There are lots of results to study dynamical complexity on irregular sets and level sets of ergodic average from the perspective of density in base space, Hausdorff dimension, Lebesgue positive measure, positive or full topological entropy (and topological pressure) etc., for example, see [52,9,51,16,67,23,5,66,28] (for topological entropy or Hausdorff dimension), [68,69] (for topological pressure), [64,38] (for Lebesgue positive measure) and references therein. However, it is unknown from the viewpoint of chaos.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, the orbits of x and y are arbitrarily close with upper density one, but for some distance, with lower density zero. ϕ-regular set and the irregular set, the union of I ϕ (f ) over all continuous functions of ϕ (denoted by IR(f )), arise in the context of multifractal analysis and have been studied a lot, for example, see [52,9,51,16,69,23]. The irregular points are also called points with historic behavior, see [57,64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The property led to fruitful results in the study of ergodic theory and qualitative theory of dynamical systems (see [1] and [5]). Recently, Dong, Oprocha and Xueting Tian [6] showed that the set of points with divergent Birkhoff averages is either empty or carries full topological entropy. Let…”
Section: Introductionmentioning
confidence: 99%